An intersectional examination of the relationship between racial/ethnic discrimination and psychotic-like experiences: the role of other psychiatric symptoms - Arielle Ered; Emily Lipner; Kathleen J. O’Brien; Zeeshan M. Huque; Deidre M. Anglin; Lauren M. Ellman (European Psychiatry)
Abstract